GERAKAN PRO DEMOKRASI DI MYANMAR - Ritayanti (HI 16 UMY 076, 2016)
*76 Movement is effort or activity in social, politic and other fields. Pro democracy movement started when a country being aware that the country that should be dependable place, secure welfare has not been able to meet their need. Pro democracy movement in Myanmar rise from various groups that want to end authoritarian military junta. The pro democracy movement has existed since English colonial era, but it had not enough power to overthrow military junta because there was minimal people knowledge about politics and there was no braveness to fight against military junta. The pro democracy movement rose strongly when there was opposition figure, Aung San Suu Kyi with higher educational background that could convince people to realize democratic state. Poverty existing in the country caused people support over the movement. The pro democracy movement was also supported by international demand against Myanmar government in form of sanction against military junta administration. So, the pro democracy movement in Myanmar was increasingly stronger due to internal factor and external factor. Key word : Movement, Democracy,Military Junta, Politics.